Найменування предметів одягу в тексті Києво-Печерського патерика - Гончаренко, А.В. (Мовознавство, 2016)
У статті розглянуто й проаналізовано номенклатуру предметів одягу та взуття в тексті Києво-Печерського патерика. Виявлено джерела походження таких мовних одиниць. Шляхом семантичного аналізу та на основі залучення діалектних даних і даних споріднених мов здійснено спробу пояснити деякі спірні значення слів. The article discusses and analyzes the nomenclature of articles of clothing and footwear in the text of Kyiv-Pechersk patericon. It is revealed the sources of an origin of such language units that demonstrate the use of lexemes, belonging to the East Slavic linguistic heritage, and borrowings from the Old Slavic, Greek and Turkic languages. The attention is paid to the phenomena of stylization of the specific lexemes which are available in the text and marked by the concepts of «artificial staroslovyanizms». An attempt of explanation of some disputable word meanings, which appeared on the periphery of language system, is made via the semantic analysis and on the basis of attraction of dialect data and data of these related languages. Separate names, on the contrary, have expanded the semantic filling. The allocation of groups of names of this kind, on the stage of early development of language, allows not just to estimate its lexical structure from a system view but also, thanking to it, to track various interrelations between separate units and groups to which they belong, in historical development and, as a result, various peculiarities of modem lexical-semantic system of language.